Non-contiguous finished genome sequence and description of Clostridium senegalense sp. nov. - Mishra, Ajay Kumar (Michigan State University, 2012)
Clostridium senegalense strain JC122(T), is the type strain of Clostridium senegalense sp. nov., a new species within the genus Clostridium. This strain, whose genome is described here, was isolated from the fecal flora of a healthy patient. C. senegalense strain JC122(T) is an obligate anaerobic Gram-positive rod-shaped bacterium. Here we describe the features of this organism, together with the complete genome sequence and annotation. The 3,893,008 bp long genome (1 chromosome but no plasmid) exhibits a G+C content of 26.8% and contains 3,704 protein-coding and 57 RNA genes, including 6 rRNA genes.